A cluster‐randomized trial comparing home‐based primary health care and usual clinic care for epilepsy in a resource‐limited country. Issue 4 (26th October 2022) - Singh, Gagandeep; Sharma, Suman; Bansal, Namita; Sharma, Meenakshi; Chowdhury, Anurag; Sharma, Sarit; Bansal, Rajinder K.; Goraya, Jatinder S.; Setia, Raj K.; Paul, Birinder S.; Sander, Josemir W.
Abstract: Objective: To ascertain whether home‐based care with community and primary healthcare workers' support improves adherence to antiseizure medications, seizure control, and quality of life over routine clinic‐based care in community samples of people with epilepsy in a resource‐poor country. Methods: Participants included consenting individuals with active epilepsy identified in a population survey in impoverished communities. The intervention included antiseizure medication provision, adherence reinforcement and epilepsy self‐ and stigma management guidance provided by a primary health care–equivalent worker. We compared the intervention group to a routine clinic‐based care group in a cluster‐randomized trial lasting 24 months. The primary outcome was antiseizure medication adherence, appraised from monthly pill counts. Seizure outcomes were assessed by monthly seizure aggregates and time to first seizure and impact by the Personal Impact of Epilepsy scale. Results: Enrolment began on September 25, 2017 and was complete by July 24, 2018. Twenty‐four clusters, each comprising ten people with epilepsy, were randomized to either home‐ or clinic‐care. Home‐care recipients were more likely to have used up their monthly‐dispensed epilepsy medicine stock (regression coefficient: 0.585; 95% confidence intervals, 0.289‐0.881; P = 0.001) and had fewer seizures (regression coefficient: −2.060; 95%CI, −3.335 to −0.785; P = 0.002). More people from clinic‐care (n = 44; 37%) than home‐care (n = 23; 19%) exited the trial ( P = 0.003). The time to first seizure, adverse effects and the personal impact of epilepsy were similar in the two arms. Significance: Home care for epilepsy compared to clinic care in resource‐limited communities improves medication adherence and seizure outcomes and reduces the secondary epilepsy treatment gap.